2017
DOI: 10.1371/journal.pone.0186190
|View full text |Cite
|
Sign up to set email alerts
|

Genomic comparison of early-passage conditionally reprogrammed breast cancer cells to their corresponding primary tumors

Abstract: Conditionally reprogrammed cells (CRCs) are epithelial cells that are directly isolated from patients’ specimens and propagated in vitro with feeder cells and a Rho kinase inhibitor. A number of these cells have been generated from biopsies of breast cancer patients, including ductal carcinoma in situ and invasive carcinomas. The characterization of their genomic signatures is essential to determine their ability to reflect the natural biology of their tumors of origin. In this study, we performed the genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…27 In CR cultures from tumor tissues, phenotypic and genotypic features of the primary tumor are maintained. 26,28 Importantly, CR tumor cells have been used to identify an appropriate therapy for a pediatric HPV-positive lung cancer and to identify both genetic and non-genetic alterations in lung tumors that correlate with patient's drug resistance pattern. 47,48 Overall, CR has been successful in generating several types of human tumor models and other human and mouse cell cultures used for various research purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In CR cultures from tumor tissues, phenotypic and genotypic features of the primary tumor are maintained. 26,28 Importantly, CR tumor cells have been used to identify an appropriate therapy for a pediatric HPV-positive lung cancer and to identify both genetic and non-genetic alterations in lung tumors that correlate with patient's drug resistance pattern. 47,48 Overall, CR has been successful in generating several types of human tumor models and other human and mouse cell cultures used for various research purposes.…”
Section: Discussionmentioning
confidence: 99%
“…27 CR induces cancer cells to grow at a rapid rate while retaining their tumorigenic properties and characteristic genetic features. 28 Overall, CR has been very successful in generating human tumor cell cultures derived from epithelial cancers. To our knowledge, this is the first demonstration of the use of this method to develop NB cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Mahajan et al. 148 characterized the molecular and cellular phenotypes of CR breast cancer cells and found that the CR cells represented the heterogeneity of primary breast tumor cells, making it a unique representative breast cancer model for further study. At present, there are many studies on female breast cancer, while only a few focused on molecular mechanisms for the development of male breast cancer.…”
Section: Cr Applicationsmentioning
confidence: 99%
“…These reprogrammed immortalized cells of malignant tumors [ 10 ], such as bladder cancer [ 11 ], prostate cancer [ 12 ], pancreatic cancer [ 13 ], breast carcinoma [ 14 ], and hepatocellular carcinoma [ 15 ], without genetic manipulation or chromosomal abnormalities, represent an adult stem-cell-like state but express fairly low levels of Sox2 , Oct4 , and Klf4 [ 16 ], which are the pluripotent progenitor markers [ 17 ]. What is more, these non-tumorigenic cells can maintain intra-tumor heterogeneity [ 18 ] in addition to keeping their molecular features [ 19 , 20 ], and are only capable of differentiating into the native tissues in which they originated [ 16 , 21 ]. Therefore, CR is appropriate to effectively assess tumor biology, screen potential therapeutic targets, and preclinically evaluate the efficiency of antitumor drugs.…”
Section: Introductionmentioning
confidence: 99%